Plutarh in Delfi - Sunčič, Maja (Monitor ISH, 2009)
The paper presents the main features of Plutarch's Pythian dialogues (The Oracles at Delphi, The Obsolence of Oracles, The E at Delphi), which are a valuable source for anthropological research because Plutarch discusses the Delphic oracle and the prophetic ability as an eye-witness. The first part of the selection from Pythian dialogues will examine some important definitions of the Pythias and Sibyls, as well as the differences between the two types of inspired prophetess, while the second will focus on Plutarch's explanation of oracular ambiguity and on the changes of the language in which Pythia pronounced the oracles.
Keywords: antična Grčija; prerokbe; preročišča; woman; ženske; Delfi